2019
DOI: 10.1371/journal.pone.0217465
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of severe exercise-associated collapse at the world’s largest half-marathon

Abstract: Background Whilst many health benefits are associated with regular exercise, medical complications may occur during higher-intensity activities, such as long distance running contests. The most common complication is collapse. However, the incidence and characteristics of these collapses are not very well studied. Method This is a retrospective study of severe collapse, defined as a patient in need of advanced medical care after a collapse, during the large Gothenburg’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 24 publications
1
14
2
4
Order By: Relevance
“…Creatinine results in collapsed and non-collapsed runners A raised serum creatinine level after a marathon is well recognised, but to our knowledge, this is the largest reported cohort of post-race serum creatinine results in collapsed marathon runners. Nearly three quarters of all collapsed runners recorded elevated serum creatinine levels, consistent with some previous smaller studies (16,24), although others suggest a much lower incidence, around 30-40% of marathon runners (11,17). However, the current study also shows comparisons to non-collapsed runners (controls) completing the same marathon course.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Creatinine results in collapsed and non-collapsed runners A raised serum creatinine level after a marathon is well recognised, but to our knowledge, this is the largest reported cohort of post-race serum creatinine results in collapsed marathon runners. Nearly three quarters of all collapsed runners recorded elevated serum creatinine levels, consistent with some previous smaller studies (16,24), although others suggest a much lower incidence, around 30-40% of marathon runners (11,17). However, the current study also shows comparisons to non-collapsed runners (controls) completing the same marathon course.…”
Section: Discussionsupporting
confidence: 91%
“…Even with these guidelines, the incidence of hyponatraemia is reported as between 8.2% (6) and 12.5%, even in asymptomatic volunteers (23). Data on serum potassium concentrations are reported less often, but hyperkalaemia has been reported in 16 % after completing a marathon (17,24). This study describes the serum sodium, potassium and creatinine changes observed in a cohort of runners immediately after a collapse during the Brighton (UK) Marathon, over a nine-year period (2010-2019) The Brighton Marathon is an annual event which has run since 2010.…”
Section: Introductionmentioning
confidence: 99%
“…blutiger Auswurf, hämodynamische Instabilität, rechtsventrikuläre Belastung, Trikuspidalinsuffizienz [ 26 ] Sofortige therapeutische Antikoagulation, Katecholamine, moderate Flüssigkeitsgabe, O 2 -Applikation, umgehende Einweisung mit Reperfusionsmöglichkeit, instabile Patienten: Lyse erwägen [ 26 ] Orthostatische Dysregulation Hypotension mit (hyperadrenerge Form) und ohne Tachykardie (hypoadrenerge Form) bzw. mit Bradykardie (neurokardiogene Form), Bewusstlosigkeit [ 22 , 27 ] Konservative Maßnahmen: Sympathomimetika, orale Flüssigkeitszufuhr, Trendelenburg-Lagerung, „begleitetes Gehen“ zur Aktivierung der Muskelpumpe (cave: Hypertension im Liegen; [ 28 ]) Schienbeinkantensyndrom Belastungsschmerz im distalen Bereich der posteromedialen Tibiakante [ 29 ] Schonung, Analgesie [ 29 ] Schwerwiegender Kollaps Tachykardie, Hyperthermie, metabolische Azidose, Hypernatriämie [ 30 ] Symptomatisch, Stabilisierung des Kreislaufs [ 30 ] Tiefe Beinvenenthrombose Schmerzen, Krämpfe, Ödematisierung, Überwärmung, Zyanose, livide Verfärbung, Ödem [ 26 ] Symptomatische Therapie, klinischer Ausschluss Lungenarterienembolie [ 26 ] Traumatische Blutung Tachykardie, Hypotension, Kaltschweißigkeit, Rekapillarisierungszeit > 2 s [ 31 ] Blutstillung (Kompression, Tourniquet, Beckenschlinge), Tranexamsäure erwägen [ 31 ] Herzrhythmusstörungen (HRST) Tachykarde HRST: > 100/min; Bradykarde HRST: < 60/min; Palpitationen, Synkope, Übelkeit, Erbrechen, ACS, Herzinsuffizienz [ 25 ] Symptomatisch, Stabilisierung des Kreislaufs, siehe ILCOR-Leitlinien [ 25 ] Prellung (Kontusion) Druckschmerz, Weichteilschwellung, Bewegungseinschränkung [ 12 , 13 ] Analgesie, abschwellende Maßnahmen, Ruhigstellung [ 12 , 13 ] Zerrung/Dehnung (Distorsion) Schmerz über der betr. Bandstruktur, Weichteilschwellung, Bewegungseinschränkung, Dehnungsschmerz [ ...…”
Section: Verletzungs- Und Erkrankungsbilderunclassified
“…Ein Großteil der Patienten benötigt keine medizinische Betreuung. Wird diese benötigt, spricht man von einem „schwerwiegenden Kollaps“ [ 30 ], der mit Tachykardie, Hyperthermie, metabolischer Azidose und Hypernatriämie als Zeichen der temporären Dehydratation einhergeht. Präklinisch stehen die ausführliche Anamnese und die Sicherung der Vitalfunktionen nach dem ABCDE-Schema im Mittelpunkt.…”
Section: Verletzungs- Und Erkrankungsbilderunclassified
“…The other stimuli for AVP release include hypovolemia, hypotension, hypoxia, hypoglycemia, strenuous exercise, and angiotensin II (Ang II; Szczepanska-Sadowska et al, 2017). The same stimuli also promote increases in pulmonary ventilation and are often associated with life-threatening conditions (Doerschug et al, 2010;Frier, 2014;Thompson et al, 2016;Convertino et al, 2019;Lüning et al, 2019).…”
Section: Introductionmentioning
confidence: 99%